Assessing school happiness: development and validation of a measurement scale for parents/guardians - Patrícia Gramaxo; Álvaro Dias; Marta Abelha; Marta Abelha; Georg Dutschke; Georg Dutschke; Filipa Seabra; Filipa Seabra (Frontiers in Education)
IntroductionParents are one of the stakeholders in evaluating schools, and families’ perspectives about schools are increasingly acknowledged as essential to educational decision-making. However, little is known about how parents’ perspectives on school happiness can be assessed. This article proposes a model for evaluating school happiness as perceived by parents/guardians.MethodsData were obtained through questionnaires administered to 641 parents. The model was tested using structural equation modeling techniques.ResultsThe results identified four main components: relationships and teachers’ characteristics (People), teaching practice (Process), learning/leisure balance (Process), and green school (Place).DiscussionThe article discusses the development and validation of an instrument that can be used with parents/caretakers as one of the means of assessing a school’s overall happiness level and identifying key aspects to improve a school’s level of happiness. Implications for future research on the evaluation of happy schools are also discussed.